Digital mediation and family climate reported by children in Spain, Italy, and Portugal - Ponte, Cristina (2023)
Considering parental mediation as a dual process that starts with the child and varies according to their age and online activities, this article examines digital socialization in the broader context of family communication. Based on the EU Kids Online questionnaire (2017-2019) which surveyed children (9-16 years old) in 19 countries, and on previous pan-European studies, the article explores results from Spain, Italy and Portugal in a comparative perspective among them and with then 19 countries average. In the three Latin countries, in line with the average, safety, support and family communication are more highlighted by children than digital socialization, which is marked by a protectionist and risk prevention approach. However, the three countries present variations in children's perceptions about their online well-being, the support they use to deal with risks and their own role in digital socialization. Acknowledging these national differences favors appropriate interventions by decision makers of public safety and well-being policies, as well as from education, health, and family counseling professionals.